2017
DOI: 10.22456/1679-9216.79386
|View full text |Cite
|
Sign up to set email alerts
|

Retrospective Study of Pneumony by Aelurostrongylus abstrusus in Cats

Abstract: Background: Aelurostrongylus abstrusus is a lungworm of cats with worldwide distribution. The adult forms of this parasite live in terminal bronchioles and alveoli, and can cause an asymptomatic disease or predominantly respiratory clinical signs, which can be occasionally cause of death. The aim of this study is to describe the epidemiological and pathological findings of infection by A. abstrusus through a necropsy retrospective study. Materials, Methods & Results: the necropsy records from the Department of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 16 publications
(24 reference statements)
0
3
0
Order By: Relevance
“…In Brazil, several states have reported this parasite, including Minas Gerais (Mundim et al 2004), Mato Grosso (Ramos et al 2013), Goiás (Campos et al 1974), Rio de Janeiro (Scofield et al 2005; Ferreira et al 2007), São Paulo (Fenerich et al 1975; Matsui et al 2018), and Rio Grande do Sul (Ehlers et al 2013; Rigão et al 2019; Ferraz et al 2020). Since this lungworm was confirmed as an important cause of death in cats in our region (Pereira et al 2017), we were motivated to study its occurrence among our patients presented with cough or evidence of bronchopulmonary disease on radiographic evaluation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In Brazil, several states have reported this parasite, including Minas Gerais (Mundim et al 2004), Mato Grosso (Ramos et al 2013), Goiás (Campos et al 1974), Rio de Janeiro (Scofield et al 2005; Ferreira et al 2007), São Paulo (Fenerich et al 1975; Matsui et al 2018), and Rio Grande do Sul (Ehlers et al 2013; Rigão et al 2019; Ferraz et al 2020). Since this lungworm was confirmed as an important cause of death in cats in our region (Pereira et al 2017), we were motivated to study its occurrence among our patients presented with cough or evidence of bronchopulmonary disease on radiographic evaluation.…”
Section: Discussionmentioning
confidence: 99%
“…It is a cosmopolitan disease and, although most cats remain subclinically infected or show mild disease (Traversa and Di Cesare 2013, 2016), intense chronic cough, dyspnea, tachypnea, wheezing, severe respiratory distress, and death may occur in severely parasitized cats (Traversa and Di Cesare 2013; Vezzosi et al 2020). A necropsy-based retrospective study conducted in Brazil showed that 22 (1.5%) of 1,489 cats were parasitized by A. abstrusus and presented different disease degrees, and this was the cause of death in 45.5% of the affected cats (Pereira et al 2017).…”
Section: Introductionmentioning
confidence: 99%
“…The discovery of A. abstrusus parasitising A. fulica in Macapá serves as an alert for veterinary medicine, given that this nematode species is a lungworm of cats with a worldwide distribution, (28) including Brazil. (23,29,30) The parasite infection rate recorded in A. fulica in the present study (94.7%, that is, 36 of the 38 snails examined were infected) was higher than those recorded in previous studies, (24) which highlights the potential role of this exotic species in the transmission of A. cantonensis and A. abstrusus both of veterinary and public health importance.…”
mentioning
confidence: 99%